Research to create a miniature generatorof technetium-99m; European Journal of Nuclear Medicine and Molecular Imaging; Vol. 42, suppl. 1 : European Association of Nuclear Medicine, EANM'15 - Rogov A. S. Alexander Sergeyevich; Skuridin V. S. Viktor Sergeyevich; Stasyuk (Stasiuk) E. S. Elena Sergeyevna; Nesterov E. A. Evgeny Alexandrovich; Ilyina E. A. Ekaterina Alekseevna (2015, 2015)
Title screen